Decol Exercises and Their Effect On the Development of Front Handspring Muscle Strength and Flexibility In Female Students - Saleh, Aamal; Fouad, Israa; Talib, Muna (Journal of Physical Education, 2019)
The research aimed at identifying the effect decol exercises on muscular strength and flexibility of front handspring in female students. The problem of the research lies in female students facing difficulty in learning gymnastics’ skill due to physical and motor abilities. The researchers used the experimental method on (20) female first Year College of physical education and sport sciences for women / university of Baghdad. The results showed the great effect of Decol exercises on developing muscle strength and flexibility in front handspring. Finally the researchers recommended developing physical abilities of female students in gymnastics as well as making similar studies.